Karakterisasi Morfologi Galur Harapan M0 dan M3 Padi Hitam Hasil Iradiasi Sinar Gamma - Nandariyah, Nandariyah; Prastyaningrum, Suci; Manurung, Ida Rumia; Sutarno, Sutarno; Riyatun, Riyatun (Agrosains : Jurnal Penelitian Agronomi, 2023)
Cempo Ireng is a black rice from Sleman that has a long harvesting period, high posture, and low productivity. Efforts to overcome these problems are mutation induction with gamma irradiation and have produced potential lines (8, 51, and 52) with early maturing, plant height 140,26 cm, and productivity 4,71 tons/ha, but not yet resistant to brown planthopper (BPH). This research is a follow-up study of 200 Gy gamma irradiation treatment of three potential lines to improve BPH resistance traits and increase genetic diversity. This study aims to determine changes in morphological characteristics and obtain superior individuals. The research was conducted in paddy field of Pakahan Village, Jogonalan District, Klaten Regency in February - July 2022 using 8:1 jajar legowo system. Observations of 25 morphological characters were carried out on 30 plants of each lines and were based on the Rice Plant Characterization and Evaluation (2003). Data analyzed by descriptively and qualitatively using Chi Square test with table value at 5% significance. The results showed there were changes in 17 morphological characters in the M3 population of black rice from gamma irradiation and individual selection resulted in 12 mutant plants.